Activating the attachment system modulates neural responses to threat in refugees with PTSD. Issue 12 (10th July 2021) - Liddell, Belinda J; Malhi, Gin S; Felmingham, Kim L; Den, Miriam L; Das, Pritha; Outhred, Tim; Nickerson, Angela; Askovic, Mirjana; Coello, Mariano; Aroche, Jorge; Bryant, Richard A
Abstract: Social attachment systems are disrupted for refugees through trauma and forced displacement. This study tested how the attachment system mitigates neural responses to threat in refugees with posttraumatic stress disorder (PTSD). Refugees with PTSD ( N  = 28) and refugee trauma-exposed controls ( N  = 22) viewed threat-related stimuli primed by attachment cues during a functional magnetic resonance imaging scan. Group differences and the moderating effects of avoidant or anxious attachment style and grief related to separation from family on brain activity and connectivity patterns were examined. Separation grief was associated with increased amygdala but decreased ventromedial prefrontal cortical (VMPFC) activity to the attachment prime and decreased VMPFC and hippocampal activity to attachment primed threat in the PTSD ( vs trauma-exposed control) group. Avoidant attachment style was connected with increased dorsal frontoparietal attention regional activity to attachment prime cues in the PTSD group. Anxious attachment style was associated with reduced left amygdala connectivity with left medial prefrontal regions to attachment primed threat in the PTSD group. Separation grief appears to reduce attachment buffering of threat reactivity in refugees with PTSD, while avoidant and anxious attachment style modulated attentional and prefrontal regulatory mechanisms in PTSD, respectively. Considering social attachments in refugees could be important to post-trauma recovery, based within changes in key emotion regulation brain systems.